The Role of Governments in Ensuring Children’s Food Security during Wartime - Sadeghinejad, Fatemeh (Bioethics and Health Law Journal (BHL), 2026)
Armed conflicts disrupt essential services, worsen poverty and pose a significant threat to children’s food security. Malnutrition among children during wartime can lead to long-term health and developmental issues. This study examines the vital role of governments in ensuring food access for children during conflicts, highlighting effective policies, interventions and challenges in mitigating hunger. A thematic synthesis was conducted to qualitatively analyze government-led initiatives aimed at ensuring sustainable food security for children. The review focused on policy frameworks, emergency food aid programs and international collaborations across three specific conflict-affected regions: South Sudan, Nigeria and Yemen. These regions were selected due to their prolonged humanitarian crises and diverse policy responses. Case studies from each region were examined to identify recurring themes, assess the effectiveness of interventions and highlight both successes and limitations in governmental approaches. Governments are crucial in tackling wartime food insecurity through emergency relief programs, school feeding schemes and partnerships with humanitarian organizations. However, logistical challenges, resource shortages and political instability often impede their effectiveness. Strategies such as decentralizing food distribution, mobilizing local food resources and integrating food security measures into post-conflict recovery plans have demonstrated promise in improving outcomes. Ensuring food security for children during wartime requires proactive government policies, efficient resource allocation and strengthened international cooperation. While short-term relief efforts are essential, long-term strategies aimed at building resilience and infrastructure are necessary to protect children’s nutrition in crisis situations. Strengthening governance mechanisms and fostering collaboration between agencies can enhance the effectiveness of food security interventions during conflicts.